Going digital: From innovation to inclusive growth in the Philippines - Francis Mark A. Quimba; Sylwyn C. Calizo (Philippine Institute for Development Studies (PIDS), 2018)
The report begins by looking at the components of the digital economy in the Philippines to understand its current landscape. These include the physical infrastructure through which data is transmitted, the devices, software and the functionalities that these offer. This description proceeds to a more detailed example of the benefits of the digital economy by looking at specific case studies particularly the TESDA online portal for e-education and the konek2CARD for e-finance. The case studies show that the inclusion of the digital economy is facilitated by developments in infrastructure. An examination of the current policy environment shows that there are key plans in place for the development of a national broadband network in the Philippines. On the demand side, policies to take care of the privacy and data of the individual users are already in place. Finally, some conclusions and policy recommendations are made to further support the digital economy in the Philippines.
Keywords: 330; digital economy; internet; broad bank; TESDA online program; digital finance; Philippines; information and communications technology; e-education; last mile consumer